Activation of SRY accounts for male-specific hepatocarcinogenesis: Implication in gender disparity of hepatocellular carcinoma. (1st December 2017) - Liu, Chang; Ren, Yi-Fan; Dong, Jian; Ke, Meng-Yun; Ma, Feng; Monga, Satdarshan P.S.; Wu, Rongqian; Lv, Yi; Zhang, Xu-Feng
Abstract: Sex affects the risk, treatment responses and outcome of many types of cancers. The mechanism of gender disparity in development of hepatocellular carcinoma (HCC) remains obscure. Sex-determining region on Y chromosome (SRY) was overexpressed in approximate 84% male patient HCC. Moreover, we are the first to generate a liver-specific transgenic (TG) murine model with overexpression of the male specific gene SRY. Subject to a single intraperitoneal injection N-nitrosodiethylamine (DEN) at day 14, TG and wildtype (WT) mice of both genders were sacrificed at different time points (6–13.5 months). Overexpression of SRY in male TG and ectopic expression of SRY in female TG livers promoted DEN-induced hepatocarcinogenesis compared to age- and sex-matched WT. This accelerated tumorigenesis in TG of both genders was a consequence of increased injury and inflammation, fibrosis, and compensatory enhancement in hepatocytes proliferation secondary to activation of downstream targets Sox9 and platelet-derived growth factor receptor α (PDGFRα)/phosphoinositide 3-kinase (PI3K)/Akt and c-myc/CyclinD1. In conclusion, activation of SRY and its downstream Sox9 and PDGFRα pathways are commonly involved in male hepatocarcinogenesis, which provides novel insights into gender disparity and sex-specific therapeutic strategies of HCC. Highlights: SRY overexpression is common in male patient HCC. Overexpression of SRY in male and female TG mice promoted hepatocarcinogenesis. Increased cellular injury and repair exacerbated liver microenvironment in TG. Activation of Sox9 induces a hepatic progenitor cell and cholangiocyte signatures. Activation of PDGFRα/PI3K/Akt and c-myc/CyclinD1 signaling is a key mechanism.